Immunohistochemical study of breast cancer antigens (part 1) - Al-Joudi, Fawwaz Shakir Mahmoud (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Survivin has been characterized as a member of the family of inhibitor of apoptosis proteins (lAP). It is a 16.5 kD protein made up of 142 amino acids. Survivin is expressed in the G2/M phase of the cell cycle. It has been previously sho\vn to be expressed in a large number of cancers, and its expression has been associated with the aggression of tumors, or with the poor survival of cancer patients.